2012
DOI: 10.3233/jad-2012-120469
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic Adenosine A2A Receptors Control the Amyloid-β Peptide-Induced Decrease of Glutamate Uptake

Abstract: Alzheimer's disease (AD) is characterized by a progressive cognitive impairment tightly correlated with the accumulation of amyloid-β (Aβ) peptides (mainly Aβ(1-42)). There is a precocious disruption of glutamatergic synapses in AD, in line with an ability of Aβ to decrease astrocytic glutamate uptake. Accumulating evidence indicates that caffeine prevents the burden of AD, likely through the antagonism of A(2A) receptors (A(2A)R) which attenuates Aβ-induced memory impairment and synaptotoxicity. Since A(2A)R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 45 publications
5
68
1
Order By: Relevance
“…This might be related to the tight interplay between APP-derived formation of Ab and the activity of glutamatergic synapses (Cirrito et al, 2008) and to the accumulation of Ab in glutamatergic nerve terminals in hippocampal regions at early stages in AD models (Lacor et al, 2004;Sokolow et al, 2012). Furthermore, several studies in different animal models of AD have converged in the identification of early dysfunctions of synaptic plasticity at cortical and hippocampal glutamatergic synapses (Hsia et al, 1999;Oddo et al, 2003;Trinchese et al, 2004;Jacobsen et al, 2006;Liu et al, 2008;Auffret et al, 2009), which result from a combined alteration of the set-up of AMPA and NMDA receptors in synapses (Almeida et al, 2005;Hsieh et al, 2006;D'Amelio et al, 2011), and from a decreased density and efficiency of astrocytic glutamate transporters Matos et al, 2012) which is also observed in the afflicted brain regions of AD patients (Hardy et al, 1987a;Westphalen et al, 2003). We now observed not only a modification of the density of vGluT1, which is compatible with a dysfunction of glutamatergic synapses, but also a reduction in the number of nerve terminals endowed with vGluT1, which is indicative of a particular vulnerability of glutamatergic terminals in early AD models.…”
Section: Discussionmentioning
confidence: 97%
“…This might be related to the tight interplay between APP-derived formation of Ab and the activity of glutamatergic synapses (Cirrito et al, 2008) and to the accumulation of Ab in glutamatergic nerve terminals in hippocampal regions at early stages in AD models (Lacor et al, 2004;Sokolow et al, 2012). Furthermore, several studies in different animal models of AD have converged in the identification of early dysfunctions of synaptic plasticity at cortical and hippocampal glutamatergic synapses (Hsia et al, 1999;Oddo et al, 2003;Trinchese et al, 2004;Jacobsen et al, 2006;Liu et al, 2008;Auffret et al, 2009), which result from a combined alteration of the set-up of AMPA and NMDA receptors in synapses (Almeida et al, 2005;Hsieh et al, 2006;D'Amelio et al, 2011), and from a decreased density and efficiency of astrocytic glutamate transporters Matos et al, 2012) which is also observed in the afflicted brain regions of AD patients (Hardy et al, 1987a;Westphalen et al, 2003). We now observed not only a modification of the density of vGluT1, which is compatible with a dysfunction of glutamatergic synapses, but also a reduction in the number of nerve terminals endowed with vGluT1, which is indicative of a particular vulnerability of glutamatergic terminals in early AD models.…”
Section: Discussionmentioning
confidence: 97%
“…The effect of A␤ astrocyte glutamate transporters and uptake is dependent on adenosine 2A receptors (A2AR). A␤ enhances expression and density of astrocytic A2AR and decreases EAAT1 and EAAT2 expression in astrocytes from wild type, but not A2AR knockout mice [233]. Expression of astrocyte EAAT2 in the hippocampus is reduced in ApoE mutant mice, suggesting inefficient glutamate uptake by astrocytes [234].…”
Section: Astrocytesmentioning
confidence: 99%
“…Through the tripartite synapse astrocytes interact with neurons (Araque et al, 1999; Halassa and Haydon, 2010) and adenosine itself affects synaptic function (Duarte et al, 2012; Matos et al, 2012a; Silva et al, 2007) with a gain of function of synaptic A 2A Rs contributing to synaptotoxicity and adaptive processes of astrocytes affecting glutamate homeostasis and thereby synaptic function (Matos et al, 2012a; Matos et al, 2012b; Matos et al, 2015). Thus, a self-reinforcing triad of astrocyte activation, adenosine dysfunction, and synaptotoxicity may contribute to the development of comorbid symptomatology.…”
Section: Introductionmentioning
confidence: 99%